In Vitro and Ex Vivo Investigation of the Antibacterial Effects of Methylene Blue against Methicillin-Resistant Staphylococcus aureus - Deniz Gazel; Mehmet Erinmez; Gönenç Çalışkantürk; Khandakar A. S. M. Saadat (MDPI AG, 2024)
Methylene blue (MB) is a water-soluble dye that has a number of medical applications. Methicillin-resistant Staphylococcus aureus (MRSA) was selected as a subject for research due to the numerous serious clinical diseases it might cause and because there is a significant global resistance challenge. Our main goal was to determine and analyze the antibacterial effects of MB against S. aureus both in vitro and ex vivo to enhance treatment options. A total of 104 MRSA isolates recovered from various clinical specimens were included in this study. Minimum inhibitory concentration (MIC) values of MB against MRSA isolates were determined by the agar dilution method. One randomly selected MRSA isolate and a methicillin-susceptible S. aureus strain (S. aureus ATCC 25923) were employed for further evaluation of the antibacterial effects of MB in in vitro and ex vivo time-kill assays. A disc diffusion method-based MB + antibiotic synergy assay was performed to analyze the subinhibitory effects of MB on ten isolates. MICs of MB against 104 MRSA isolates, detected by the agar dilution method, ranged between 16 and 64 µg/mL. MB concentrations of 4 and 16 µg/mL showed a bactericidal effect at 24 h in the ex vivo time-kill assays and in vitro time-kill assays, respectively. We observed a significant synergy between cefoxitin and methylene blue at a concentration of 1-2 μg/mL in two (20%) test isolates. Employing MB, which has well-defined pharmacokinetics, bioavailability, and safety profiles, for the treatment of MRSA infections and nasal decolonization could be a good strategy.